Получение нового радиофармпрепарата на основе D-глюкозамина, меченого технецием-99м; Известия вузов. Физика; Т. 58, № 2-2 - Скуридин В. С. Виктор Сергеевич; Ильина Е. А. Екатерина Алексеевна; Стасюк Е. С. Елена Сергеевна; Рогов А. С. Александр Сергеевич; Нестеров Е. А. Евгений Александрович; Садкин В. Л. Владимир Леонидович; Ларионова Л. А. Людмила Александровна (2015, 2015)
Заглавие с экрана